IoT in Courier Services: Impact on Customer Satisfaction and Supply Chain Sustainability - Prapinit, Pichit; Kafi, Md. Abdul; Osman, Nor Hasni; Melan, Mustakim (International Information and Engineering Technology Association, 2024)
The increasing importance of integrating the Internet of Things (IoT) within the courier service sector in today's digital landscape highlights the necessity for an in-depth examination of how IoT intricately affects customer satisfaction and the sustainability of supply chains in this industry. The objective of this study is to assess the impact of IoT on both customer service and the sustainability of supply chains, with a specific focus on electronic document management, route optimization, and real-time information. A random sampling survey technique was employed to collect data from 310 participants in the Malaysian courier service company in the year 2022. The data analysis primarily relied on quantitative methods, with the utilization of multiple regression analysis as a key technique for evaluating the effects. The outcomes of this study provide validation for our hypotheses concerning the positive influence of electronic document and route optimization, while also emphasizing the critical aspect of managing real-time information. These findings contribute invaluable insights for courier service companies striving to harness the capabilities of IoT to enhance service quality and promote sustainable operations. Future research directions may delve deeper into the intricate dynamics of IoT's role to explore its scalability and cost-effectiveness within courier service companies